A biocompatible two-photon absorbing fluorescent mitochondrial probe for deep in vivo bioimaging. Issue 6 (13th January 2022) - Lin, Lingmin; He, Zewei; Zhang, Tianfang; Zuo, Yanming; Chen, Xiangfeng; Abdelrahman, Zeinab; Chen, Feihong; Wei, Zhongcao; Si, Ke; Gong, Wei; Wang, Xuhua; He, Sailing; et al.
Abstract : We reported a mitochondria-targeted two-photon fluorescent dye with an excellent two-photon absorption cross-section. With this dye, we reached an imaging depth of ca. 640 μm during mitochondrial imaging of cortical cells in live animals. Abstract : Mitochondria, key organelles which keep in tune with energy demands for eukaryotic cells, are firmly associated with neurological conditions and post-traumatic rehabilitation. In vivo fluorescence imaging of mitochondria, especially with deep tissue penetration, would open a window to investigate the actual context of the brain. However, the depth of traditional two-photon mitochondrial fluorescence imaging is still limited due to the poor biological compatibility or low two-photon absorption cross-sections. A biocompatible mitochondria-targeted two-photon fluorescent dye (FO2 ) with an excellent two-photon absorption cross-section (the maximum of 1184 GM at 790 nm) and low cellular toxicity was designed and synthesized to overcome this problem. With this dye, we reached an imaging depth of ca. 640 μm during mitochondrial imaging of cortical cells in live animals. FO2 could be an excellent mitochondrial probe for live animal neural imaging to investigate the function and dysfunction of mitochondria in the brain.